Treatment of reindeer with ivermectin - effect on dung insect fauna - Nilssen, Arne C.; Åsbakk, Kjetil; Haugerud, Rolf Egil; Hemmingsen, Willy; Oksanen, Antti (Rangifer, 1999)
Ivermectin is an antiparasitic drug widely used in reindeer (Rangifer tarandus (L.)) in Fennoscandia and North America. Most of the ivermectin injected in the animal is excreted unchanged in the faeces. Several reports show that ivermectin in cattle dung disrupts colonisation and survival of beneficial dung breeding insects. The present study investigated the effect of ivermectin on the reindeer dung fauna. Four reindeer calves (males, 6 months of age) were injected subcutaneously with standard doses of ivermectin (0.2 mg/kg body weight) in early December. The daily produced faeces was collected until day 30 after treatment, and the concentration of ivermectin was determined by high pressure liquid chromatography (HPLC) with fluorescence detection. The highest concentration measured (mean 1632 ng/g faeces (dry weight), range 907 to 2261 ng/g among the animals) was on day 4 after treatment. The concentration decreased gradually to 28 ng/g (range 6 to 58 ng/g) on day 30. Faeces portions from day 4 and from untreated reindeer were placed in the field on 2-4 July and recollected on 13-22 September in order to detect possible differences in decomposition fauna between the samples. The most important coprophilous beetles (Apbodius spp.) and flies (Scatbophaga spp.) were not detected in this winter dung whether it contained ivermectin or not, probably because of the dry consistency and small size of the pellets. On the other hand, these insects (larvae and imagines) were common in summer dung, which had been deposited naturally in the field and later placed together with the ivermectin-containing winter dung for comparison. The summer dung has a more soft and lumpy consistency. Treatment in autumn or early winter implies that the bulk of the ivermectin from the animal will be present in faeces with winter consistency, since this bulk portion is excreted during the first 30 days after treatment. This dry and pelleted faeces is not utilized by the important coprophilous insecr species, and the current practice of treatment of reindeer with ivermectin in autumn or early winter is therefore the regime representing the least danger of harmful influence on the coprophilous fauna and their contribution to the dung decomposition process.